Effect of spinning parameters on PLA/PPC/curcumin microfiber diameter: An investigation via response surface methodology - Shaharuddin S.I.S.; Fauzan A.A.; Jazi M.F.I.M.; Akhir N.A.M.; Othman M.; Khairussaleh N.K.M.; Shaffiar N.; Hasan Z. (International Islamic University Malaysia-IIUM, 2023)
The initial phase of this study was to investigate the effect of polypropylene carbonate (PPC) additions in polylactic acid (PLA)/curcumin (Cur) blends. It was observed that the presence of curcumin particulates behaved as a reinforcement filler for PPC additions up to 30 wt%. A specific composition was then invested to find the correlation between the fiber diameter and melt-spinning process parameters using central composite design (CCD), a subset of response surface methodology (RSM). Results showed that the spinning temperature had a greater effect than the spinning speed on the diameter of PLA/PPC/curcumin fiber. The response model indicated a good correlation between experimental and predicted values since the ANOVA analysis demonstrated high Fvalue of model adequacy at 10.34, non-significant lack of fit, precision adequacy of 9.94 and R2 value of 0.80. Therefore, this model can be used in a future study to establish the processing parameters for controlled fiber production. 2020, International Islamic University Malaysia-IIUM.